2019
DOI: 10.1016/j.dhjo.2018.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the timing of first sexual experiences among populations with physical disabilities in the United States

Abstract: Background Timing of first sex has important implications for later sexual health, but little research has considered this in populations with physical disabilities. Objective/Hypothesis The purpose of this paper was to examine timing of sexual experiences among populations with physical disabilities in the United States from adolescence to early adulthood, and how timing varies by biological sex, race/ethnicity, and sexual orientation. We hypothesized that those with physical disabilities would exhibit earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Regarding sexual behaviors, kissing, touching, and caressing, receiving stimulation of erogenous zones and performing oral sex were the most frequently reported sexual activities by participants. This finding is supported by the results of earlier studies [29][30][31], which indicated that people with physical disabilities have significantly lower odds of partaking in sexual activities that involve penetration and greater chances of not engaging in sex, at all. Nevertheless, the vast majority of those who reported not having sex stated that this was because of a lack of opportunity or lack of a partner.…”
Section: Discussionsupporting
confidence: 77%
“…Regarding sexual behaviors, kissing, touching, and caressing, receiving stimulation of erogenous zones and performing oral sex were the most frequently reported sexual activities by participants. This finding is supported by the results of earlier studies [29][30][31], which indicated that people with physical disabilities have significantly lower odds of partaking in sexual activities that involve penetration and greater chances of not engaging in sex, at all. Nevertheless, the vast majority of those who reported not having sex stated that this was because of a lack of opportunity or lack of a partner.…”
Section: Discussionsupporting
confidence: 77%
“…The increased vulnerability of minors with disabilities to minor sex trafficking fits within the broader context of research on the cycle of child disability and maltreatment, which depicts children with disabilities as more vulnerable to experience various forms of maltreatment. Other literature has shown that children with various forms of disabilities have higher risk of experiencing abuse and neglect in general, including sexual abuse, can experience more severe offenses of sexual abuse, and have higher incidence of maltreatment that resulted in serious harm (Haydon et al, 2011;Hershkowitz et al, 2007;Kahn et al, 2019;Schenkel et al, 2014;Sedlak et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Physical disability. Physical disabilities were assessed using the physical disability index (PDI) developed by Cheng and Udry (2002) using data from the Wave I survey, a measure that has been used successfully in other research studies (Haydon et al, 2011;Kahn et al, 2019). During in-home interviews with adolescents and parents, physical disabilities were identified via a series of questions on blindness, deafness and long term/permanent difficulties using hands, arms, legs or feet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, individuals identified as having "low cognitive abilities" appeared less likely to be sexually active during adolescence or early adulthood compared with peers with average cognitive abilities [6,7]. Evidence on the timing of first sexual contact has been mixed, with some studies finding no difference between individuals with mild to moderate disabilities and those with no disabilities [8,9], while others have reported a higher prevalence of early sexual intercourse among youth with disabilities [10,11]. Among teens who are sexually active, those with disabilities may be more likely to have multiple sexual partners or have condomless sex than youth without disabilities [5,6], but more current research is needed in this area.…”
Section: Implications and Contributionmentioning
confidence: 99%